Pharmacoeconomic Assessment of the Application of Dornase Alfa in the Treatment of Lung Generation in Patients with Cystic Fibrosis - Zaytzeva, Yuliya L. (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Cystic fibrosis (CF) is an important medical and pharmaceutical, social and economic problem both in the whole world and in Ukraine. Effective and safe, well-grounded health technology (HT) is needed to increase the availability of highly qualified medical and pharmaceutical care to patients with CF in Ukraine for the purpose of survival rate, recovery and life expectancy of patients increasing. Materials and Methods: Taking into account the aforementioned goal of our study, we have conducted a pharmacoeconomic assessment of the dornase alfa usage in the treatment of pulmonary exacerbations in patients with CF. We included data for this outcome from trials lasting 1 month, 6 months and 2 years (dornase alfa n = 575, control n = 576)[9]. This yielded a risk ratio of 0.78 (95% confidence interval 0.62â€“0.96) in favor of dornase alfa. Results: It has been established that in the inhalation use of the dornase alfa (2.5 mg 1 time a day) in adults and children over 5 years ago, the absolute risk of pulmonary exacerbations in patients with CF was 19.5%, without dornase alfa - 25.2%. That is, in 195 patients form a thousand of CFâ€™ patients who took dornase alfa, there were pulmonary exacerbations.[9] The frequency of pulmonary exacerbations in the treatment with dornase alfa per year was 1.25, and in non-dornase alfa â€“ 3,13. Consequently, taking into account the data of the systematic review in the subsequent calculations, the annual period of use of the dornase alfa in the treatment of pulmonary exacerbations of patients with CF has been taken. It should be noted, that the total direct medical costs of the application of HT-1 (dornase alfa) in the treatment of pulmonary exacerbations in CF children aged 5â€“18 years have been in 2.7 times more comparing to the HT-2 (without dornase alfa). It has been established that the most cost-effective in the treatment of pulmonary exacerbations in children aged 5â€“18 years with CF is the use of HT-1. Direct medical costs for children aged 5â€“18 years with the use of HT-2 are 17% higher than with the use of HT-1. Thus, the use of HT-2 in children aged 5â€“1z8 years requires additional direct medical expenses of 245061.44 USD. Calculation of the coefficient of â€œlost opportunityâ€ allowed to establish, in the course of the year, the use of dornase alfa in the treatment of patients with CF may additionally allows to treat almost 37 children diagnosed with CF. The BIA of direct medical expenses for the treatment of pulmonary exacerbations in patients with CF (for the predicted number of patients) for 2017â€“2021 has shown significant benefits of HT-1 (dornase alfa). Hence, in 2018, the total savings of budget funds will be 265 331.91 USD, in 2019â€“271 689.08 USD., in 2020â€“291 015.04 USD., and in 2021â€“310,340.99 USD (the average growth rate of budget savings for 2017â€“2021 will be 1.06). Discussion: There was not any study that describes pharmacoeconomic assessment of the application of dornase alfa in the treatment of lung generation in patients with CF for Ukraineâ€™ conditions before. Conclusion: Consequently, pharmacoeconomic studies, conducted by us, allows to formulate a rational financial policy and promote the realization of the rights of the child patient with the CF for obtaining a pharmacotherapy that meets the modern international recommendations.